The Effect of Distraction Therapy in Reducing Children's Anxiety During Circumcision: Pengaruh Terapi Distraksi dalam Mengurangi Kecemasan pada Anak yang Disunat - Rahmawati, Primasari Mahardhika; Sulistyono, R. Endro; Suhari; Ochta Pebriyanti, Dwi (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2024)
Circumcision or circumcision is a surgical procedure that involves removing all or part of the foreskin of the penis with the aim of keeping the vital area clean so that it is not easily infected. By 2020, 85% of boys will be circumcised, equating to around 8.7 million boys annually. The circumcision rate will increase along with population growth in Indonesia. Most children who undergo circumcision will encounter obstacles such as fear, crying, refusing to enter the room and having to ask their parents to accompany them when they want to enter the room. This shows that there are fundamental problems in children who will be circumcised. Anxiety is one of the things a child will face before being circumcised. Anxiety can cause prolonged trauma, causing children to experience stressor crises. The cause of anxiety is pain and fear during the circumcision process. Often parents and medical personnel think this is trivial, but in fact if left unchecked it will have a serious impact on the child's mental condition. Distraction therapy is an example of therapy that can help reduce a child's anxiety about circumcision. Children who are circumcised will naturally feel afraid and anxious, so play therapy is carried out to reduce these feelings of anxiety. This therapy involves diverting attention to the child who will be circumcised. The goal is to change the child's orientation and thinking, which was initially focused on circumcision, towards the proposed therapy. This will create a feeling of security and comfort, thereby helping the circumcision process run smoothly.